Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species (Tree Physiology, 2004)
Photoinhibition was examined in four co-occurring Mediterranean evergreen tree species during two consecutive winters. In response to low temperatures and saturating light, Juniperus phoenicea L., Pinus halepensis Mill., Quercus coccifera L. and Q. ilex ssp. ballota (Desf.) Samp. exhibited marked chronic photoinhibition, indicated by low predawn maximal photochemical efficiency of photosystem II (PSII) (Fv/Fm). Low Fv/Fm values were correlated with high concentrations of xanthophyll cycle components (VAZ) and with the maintenance of high concentrations of zeaxanthin overnight (DPSpd). In all species, however, chronic photoinhibition was enhanced as the winter progressed in the absence of changes in DPSpd, suggesting cumulative damage toward the end of winter.Photoinhibition differed among species: P. halepensis always displayed significantly higher Fv/Fm values; and Q. coccifera had the lowest Fv/Fm values, showing a high sensitivity to the combination of high light and low temperatures. Differences among species were not fully explained by differences in the xanthophyll pool or its de-epoxidation state. Chronic photoinhibition overlapped with a dynamic photoinhibition as shown by the low values of photochemical efficiency of the open reaction centers of PSII at midday. Winter photoprotective strategies differed among species and may involve photoprotective mechanisms in addition to those associated with xanthophylls. The observed species-specific differences matched results obtained for the same species in summer; however, comparison of the two seasons suggests that the higher VAZ concentration observed in winter has an additional structural photoprotective role.
From Duplicate 2 (Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L)